Writing News Item in English Language Teaching Context: Line Apps Platform for Senior High School Students - Tia Dwi Risani (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
Learning English nowadays is a process of giving learners not just skills its also an innovative learning technique, and creative ways are needed as well. The Information Communication Technology (ICT) device such as social media, i.e., Line provides students to explore more in learning English. This research aimed at proving social media such as Line today can be used as virtual support for English language Teaching (ELT) process of writing news item in senior high school. This descriptive qualitative research was conducted on classroom during the subject news item. In this study, the research belongs to the interpretivism paradigm or related to the explaining or understanding the meaning of a sentence or passage. The result of this research is using a virtual or electronic device not only could help students as a learner but the essential things in learning process namely teachers also need virtual to support teaching process and even virtual assessment help teachers and even students to develop learning process especially by using Line apps for writing news item.